NUTRITION IN PREGNANCY - Fitria; Risna Fazlaini; Dewina Susanti; Nizam Mauyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Based on the mid upper arm circumference, 23.9% of the pregnant women were found to be undernourished (MUAC < 23.0 cm). The Ministry of Health announced the results of the Indonesia Nutrition Status Survey (INSS) at the National Family Planning Coordinating Board (BKKBN) National Working Meeting, where the prevalence of stunting in Indonesia decreased from 24.4% in 2021 to 21.6% in 2022. Researchers conducted a systematic search using a computer and explored the electronic databases PubMed in November 2023. Using PRISMA procedures, a systematic review was conducted by searching in biomedical databases clinical trials and interventions for pregnant women. The PubMed Central search strategy yielded a total amount of 386 articles. Based on the analysis, optimizing weight gain during pregnancy according to IOM recommendations includes maintaining a normal BMI at the beginning of pregnancy. First, clinicians should assess the mother's pre-pregnancy weight, recommend weight gain during pregnancy, and create a weight gain plan during pregnancy by developing a curve or graph. Second, individual assistance and counseling are provided before and during pregnancy to help mothers choose a diet and physical activity that play a role in controlling weight gain. Third, assisting mothers in returning to normal BMI postpartum. Fourth, the increase in daily calorie requirements is only about 340 Kcal/day in the second trimester and 450 Kcal/day in the third trimester. For multiple pregnancies, the increase in calories is calculated based on per fetus, requiring an additional 300 Kcal/day.